2017
DOI: 10.1080/10826084.2017.1365087
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Beverage Cues as Specific Comparison Images to Alcohol Image Cues

Abstract: We conclude that the choice of control cues in alcohol cue-reactivity studies is important, and that the currently developed non-alcoholic beverage cue set provides an adequate control for alcohol beverage cues for use in cue-reactivity paradigms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The AI-funded bodies were significantly more likely to use alcohol and drinking images. Alcohol/drinking images have been shown to act as a cue to alcohol craving and drinking [50,51,52], and it has also been found that alcohol information materials encouraging ‘responsible drinking’ can have the opposite effect, by encouraging drinking [7,31]. The use of images, in the absence of explicit advertising, and their impact is well documented by studies of tobacco industry (strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The AI-funded bodies were significantly more likely to use alcohol and drinking images. Alcohol/drinking images have been shown to act as a cue to alcohol craving and drinking [50,51,52], and it has also been found that alcohol information materials encouraging ‘responsible drinking’ can have the opposite effect, by encouraging drinking [7,31]. The use of images, in the absence of explicit advertising, and their impact is well documented by studies of tobacco industry (strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Stimuli for the CS 1 consisted of alcohol and non-alcohol beverage containers photographed in a real-world context: a wooden table with wooden booth-style seating typical of pubs and restaurants. These were taken from a standardized picture set for alcohol cue reactivity studies, from which most, but not all, overt branding elements have been removed and which has been validated for alcohol craving induction in American adults (Lovett et al, 2015 ; Veilleux et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%